Analisis perbandingan efektifitas aturan dalam Kitab Undang Undang Hukum Pidana lama dan Revisi Kitab Undang Undang Hukum Pidana (khususnya dalam pasal perzinahan) - Nur Shabrina Sinulingga (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2019)
The Criminal Code (KUHP) which is currently in force in Indonesia is a legacy that is still inherited from the Netherlands, so some of the contents of the Article are still incompatible with the culture that developed in Indonesia. One example of the definition of adultery in the Criminal Code is a marital relationship which is committed by a party that one or both are still bound in marriage. Of course this is very contrary to the culture that exists in Indonesia with a majority Muslim population. Indonesian legal experts have drafted the new Criminal Code since 50 (fifty) years ago, then after waiting all the time, finally in 2019, there is a strong discourse that the DPR (House of Representatives) will ratify the new Criminal Code. One of the revised articles in the RKUHP (draft of the Criminal Code) is this adultery article. However, this Article is one that is also a matter of controversy and much opposition.The old KUHP rules especially those relating to adultery are not in accordance with the culture that exists in Indonesia, so that frequently the act of adultery that actually disturbs the public cannot be tried as expected, but in the current development there are also many parties who consider the notion of adultery in the new KUHP too in entering into the private affairs of the Indonesian people they assume the State should not enter into a very private section.The legal basis that can be done is a legal basis that is in accordance with that contained in the Criminal  Code Keywords: Criminal Code, Adultery